2020
DOI: 10.1530/ec-20-0444
|View full text |Cite|
|
Sign up to set email alerts
|

Simvastatin profoundly impairs energy metabolism in primary human muscle cells

Abstract: Objectives: Simvastatin use is associated with muscular side effects, and increased risk for type 2 diabetes (T2D). In clinical use, simvastatin is administered in inactive lipophilic lactone-form, which is then converted to active acid-form in the body. Here, we have investigated if lactone- and acid-form simvastatin differentially affect glucose metabolism and mitochondrial respiration in primary human skeletal muscle cells. Methods: Muscle cells were exposed separately to lactone- and acid-form simvastatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Primary muscle cell cultures were established from vastuslateralis muscle biopsies ( Skrobuk et al 2012 , Mäkinen et al 2020 ). Myoblasts were differentiated into multinucleated myotubes for 6–7 days in low glucose (5.6 mmol/L) DMEM/F12 containing 2% (v/v) FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary muscle cell cultures were established from vastuslateralis muscle biopsies ( Skrobuk et al 2012 , Mäkinen et al 2020 ). Myoblasts were differentiated into multinucleated myotubes for 6–7 days in low glucose (5.6 mmol/L) DMEM/F12 containing 2% (v/v) FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular signalling targets were investigated in differentiated myotubes with Western blotting ( Skrobuk et al 2012 , Mäkinen et al 2020 ), by detecting the phosphorylated and corresponding total proteins with antibodies, which were visualized by enhanced chemiluminescence and quantified using Fiji software ( Schindelin et al 2012 ) (for signalling targets AKT, AS160 and GSK3β) or Image Lab software (Bio-Rad) (for signalling targets MNK2, eIF4E and FAK) ( Supplementary Material ). Unless otherwise noted, intensities of the phosphorylated proteins were normalized to the intensity of their corresponding total protein and data were normalized to the basal control sample of each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Sambubioside) [15]. Additionally, qualitative analysis has been utilized through the Thin Layer Chromatographic technique, reporting that each leaf, seed, flower, and root of HS contains the primary and secondary metabolites in the form of alkaloids and flavonoids phenolics, saponins, and glycosides [16].…”
Section: The Content and Benefits Of Hibiscus Sabdariffa As A Herbal ...mentioning
confidence: 99%
“…In addition, several studies have reported that phenolic compounds are the most abundant compounds contained in HS. Particularly, flavonoids are regarded as one of the most abundant phenolic compounds in all parts of HS, acting as antioxidant agents [14,16]. Flavonoids are also beneficial in lowering oxysterols (cholesterol derivatives) in bile acid metabolism, blocking fat accumulation in the liver.…”
Section: The Content and Benefits Of Hibiscus Sabdariffa As A Herbal ...mentioning
confidence: 99%
“…This novel therapeutic approach, based on the regulation of membrane lipid structure, is referred as Membrane Lipid Therapy, and is evolving rapidly due to its potential use in the treatment of several human disorders [10]. The contemporary use of both acid and lactone form of statins is an increasingly common strategy in scientific studies, and can contribute to a better understanding of the mechanisms behind statin uptake, metabolism and occurrence of pleiotropic effects [11,12] (Figure 1).…”
mentioning
confidence: 99%